2019
DOI: 10.1177/1833358319839253
|View full text |Cite
|
Sign up to set email alerts
|

Development of an evidence-based e-health readiness assessment framework for Uganda

Abstract: Background: While e-health readiness assessment is vital to the successful implementation of e-health innovations, there is little published guidance (i.e. e-health readiness assessment frameworks (eHRAFs)) for institutions and countries. Objective: To develop an evidence-based and locally relevant eHRAF for Uganda. Method: A list of possible e-health readiness domains and constructs was developed through a structured review of the e-health literature. This list was first refined using author experience, insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The components of the framework were derived from key technology readiness assessment frameworkrelated studies on blockchain (Ozturan et al, 2019;Vlachos et al, 2019), e-health (Li et al, 2012;Rezai-Rad et al, 2012;Kiberu et al, 2019), e-records (Malanga and Kamanga, 2019), cloud computing (Colicchio et al, 2015), enterprise resource planning (Razmi et al, 2009), and e-government (Shareef et al, 2008).…”
Section: Components Of the Assessment Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The components of the framework were derived from key technology readiness assessment frameworkrelated studies on blockchain (Ozturan et al, 2019;Vlachos et al, 2019), e-health (Li et al, 2012;Rezai-Rad et al, 2012;Kiberu et al, 2019), e-records (Malanga and Kamanga, 2019), cloud computing (Colicchio et al, 2015), enterprise resource planning (Razmi et al, 2009), and e-government (Shareef et al, 2008).…”
Section: Components Of the Assessment Frameworkmentioning
confidence: 99%
“…However, a sector-wide implementation of any disruptive technology (such as blockchain) is challenging. Assessing the "readiness" for new technology projects is critical; unanticipated challenges during implementation may result in failure (Razmi et al, 2009;Kiberu et al, 2019). Given that blockchain is only as strong as its weakest link, understanding the differences in the readiness of the sector's stakeholders is critical (Pólvora et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Lacking digital skills to operate a system can be aggravated by the little or no formal education. As reported in other studies [20], [24], [37], [40] the lack of ICT skills to operate digital technologies was a very big impediment to adoption. Whereas a study conducted in Finland indicated that digital literacy does not have a direct impact on adoption [58], research conducted in Uganda, found out that expectant mothers did not use digital health technologies in their routine antenatal care practices because they lacked technical skills to operate the internet, computers and smartphones [29].…”
Section: Discussionmentioning
confidence: 55%
“…A structured survey questionnaire formulated in English with three main themes (demographic data, barriers and facilitators) was used to collect data. Barriers and facilitators used in the questionnaire were drawn from existing studies [6], [19], [23], [28], [37]- [39], [21], [27], [29], [16], [22], [32], [30], [40], [41], [20], [33], [42], [10]. All authors designed the questionnaire, however it was specifically tailored to fit the scope of this study.…”
Section: Methodsmentioning
confidence: 99%
“…However, these studies are mostly related to normal health care operations. In a few studies [10,11], frameworks were developed for health care management during pandemics; however, these studies are limited in scope, focusing on frameworks for assessing preparedness and readiness but not for managing health care operations during pandemics. These studies focused on readiness strategies, such as resource management, finances, and vaccination; none of them highlighted an operational framework for pandemics that includes eHealth approaches or stakeholders' roles and responsibilities.…”
Section: Introductionmentioning
confidence: 99%